Popular Songs and Ballads of Han China - Birrell, Anne (University of Hawai'i Press, 2018)
The oral factor in Chinese literature, although critically important, has been largely neglected in the scholarship of the last generation. In this study, one of the leading specialists in classical Chinese literature introduces readers to a repertoire of seventy-seven songs and ballads of early imperial China. Each song-text is newly translated and fully annotated and explicated. Anne Birrell deals systematically with problems of the earliest sources, attribution, textual variants, meter, and structure. Her introductory essay provides a valuable sociohistorical context for this material. First published in 1988, this important study of the folk song has become standard reading for students of oral literature and Chinese folklore and popular culture.